A clinical case of using ICG-technologies to evaluate the results of the superior mesenteric artery stenting in a patient with acute mesenteric ischemia - A. G. Khitaryan; A. S. Murlychev; I. V. Bondarenko; S. A. Kovalev; K. S. Veliev; A. A. Orekhov; A. Z. Alibekov; A. V. Mezhunts; A. A. Golovina (Амбулаторная хирургия, 2020)
Introduction. Acute mesenteric ischemia is a rare, but extremely severe life-threatening condition with a mortality rate of 40 to 60%, despite the development of modern high-tech diagnostic and treatment methods. Unfortunately, acute mesenteric ischemia does not have any pathognomonic symptoms or highly specific laboratory and instrumental symptoms and manifests as abdominal pain syndrome, which makes it harder to differentiate diagnosis and results in a delay in taking appropriate therapeutic measures.Clinical case. This clinical case report describes a case of a 70-year-old patient who was admitted to the cardiology department after undergoing percutaneous coronary intervention due to acute myocardial infarction. On the third day, the patient developed severe diffuse abdominal pain and diarrhea. After the series of diagnostic measures have been performed, an acute impairment of mesenteric circulation was suspected and a decision was made to perform spiral computed tomography, which confirmed the presence of a thrombus in the superior mesenteric artery. The patient underwent X-ray endovascular thrombospiration, transluminal balloon angioplasty and stenting of the superior mesenteric artery. Due to the persistence of abdominal pain on the following day, the patient also underwent a diagnostic laparoscopy using ICG technologies to assess the presence and severity of ischemic and necrotic intestinal changes. After six months from the date of discharge, the patient continues to be followed-up by a cardiologist.Conclusions. The timely performance of spiral computed tomography in patients with suspected acute mesenteric ischemia in the vascular regimen, angiography, endovascular interventions to restore blood supply to the intestine and ICG control of perfusion is appropriate to improve the treatment outcomes of this category of patients.